Some Aspects of Mode Interaction in Thin-Walled Stiffened Plate Under Uniform Compression - Z. Kołakowski (Engineering Transactions, 1988)
Interaction of nearly simultaneous buckling modes in the presence of imperfections is studied. The investigation is concerned with infinitely wide plate with thin-walled stiffeners under uniform compression. The asymptotic expansion established by BYSKOV and HUTCHINSON [1] is also used here. The present paper is devoted to the improved study of equilibrium path in the initial postbuckling behaviour of imperfect structures. The results include effects of interaction of the „primary" local mode and a „secondary" local mode having the same wavelength as the primary one. In this paper the analysis of a few buckling modes interaction is presented.